A novel passive system for providing natural ventilation and passive cooling: Evaluating thermal comfort and building energy. (October 2022) - Moghtader Gilvaei, Zoleikha; Haghighi Poshtiri, Amin; Mirzazade Akbarpoor, Ali
Abstract: Hybridization of natural ventilation with the passive cooling technique is a feasible approach for reducing the dependency on energy-consuming mechanical HVAC systems. The present study numerically investigated the viability of the application of a novel hybrid system composed of a windcatcher, an earth-to-air heat exchanger (EAHE), and a direct evaporative cooling system in a residential building. The test building was a two-story apartment with an area of 100 m 2 (each floor 50 m 2 ). 3-D Computational Fluid Dynamics (CFD) simulations were conducted to determine the airflow characteristics inside and outside the test apartment. Moreover, a computer program was developed and validated with the literature for modeling the thermal performance of the system. The effects of the environmental conditions (wind speed, ambient temperature and relative humidity, and average soil temperature) and the windows opening on the performance of the system were evaluated. The obtained results provided a design guideline that determines the allowable windows opening range for providing the thermal comfort conditions in the test rooms. The studied passive system could fulfil the comfort criteria for the test building under a maximum cooling load of 10000 W and 6500 W, according to adaptive thermal comfort standards (ATCS) and ISO7730, respectively. Finally, the energy metric and environmental analysis were carried out to compare the introduced system with the conventional mechanical cooling equipment during the hot months of the year. It was concluded that utilizing the proposed system could lessen the hourly electrical energy consumption by 0.0194 kW h/m 2 compared to split air conditioners and 0.0081 kW h/m 2 in comparison with evaporative coolers, resulting in a 20.2815 kg/m 2 and 8.4681 kg/m 2 annual reduction in CO2 emission, respectively. Graphical abstract: Image 1